2021
DOI: 10.1097/md.0000000000027380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognosis predictive value of 4 disease severity scoring systems in patients with acute respiratory failure in intensive care unit

Abstract: Various disease severity scoring systems were currently used in critically ill patients with acute respiratory failure, while their performances were not well investigated. The study aimed to investigate the difference in prognosis predictive value of 4 different disease severity scoring systems in patients with acute respiratory failure. With a retrospective cohort study design, adult patients admitted to intensive care unit (ICU) with acute respiratory failure were screened and relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In addition, we also included in the regression model of the OASIS the Scr levels as predictors of AKI in diabetes. A study showed that the OASIS had a good predictive effect on the assessment and prognosis of critically ill patients (41). The baseline Scr values could also predict the occurrence and progression of AKI (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also included in the regression model of the OASIS the Scr levels as predictors of AKI in diabetes. A study showed that the OASIS had a good predictive effect on the assessment and prognosis of critically ill patients (41). The baseline Scr values could also predict the occurrence and progression of AKI (42).…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review showed that the SOFA model based on 24 h after ICU admission could be used to predict mortality ( 19 ). Other types of patients were also effectively evaluated by SOFA score, including post-cardiac arrest syndrome ( 20 ), people requiring extracorporeal cardiopulmonary resuscitation ( 21 ), critically ill cirrhotic patients with acute decompensation ( 22 ), patients with acute respiratory failure in intensive care unit ( 23 ), contemporary cardiac intensive care unit population ( 24 ), critically ill elderly patients with acute infective endocarditis ( 25 ), extracorporeal membrane oxygenation (ECMO)-treated acute myocardial infarction (AMI) patients ( 26 )—some of above studies behaved even well. In the cardiac surgery population, the previous literature stated that SOFA score had good discriminative power for hospital mortality ( 27 ); the same observation was also confirmed in Ceriani et al's research ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 It is composed of clinical variables collected within the first 24 hours of admission to an ICU and shown to have strong prognostic value in MIMIC-III. 32,33 Higher scores represent worse prognosis and illness severity.…”
Section: Covariatesmentioning
confidence: 99%